How Does Managerial Ability Affect Cost of Equity Capital? - Arslan, Volkan (Université d'Ottawa / University of Ottawa, 2022)
This research will contribute the literature of managerial ability and cost of capital. This study is the first to investigate the association between managerial ability and cost of capital to the best of our knowledge using Demerjian et al. (2012). Managerial ability is the measurement methodology which is the most commonly used method to evaluate the managerial ability in the literature. In a previous study, Mishra (2014) investigates the relation between CEO managerial ability and cost of capital by using Custodio’s (2013) CEO managerial ability methodology. This method only measures the ability of CEOs based on their experience. Those who have several experiences in different departments and other sectors are regarded as generalist CEOs, while some others who have one specific experience in a department and/or sector are regarded as specialist CEOs. Mishra shows a positive relation between generalist CEOs and cost of capital; it is regarded as the dark side of managerial ability. Mishra explains this relation by the risky behaviors of generalist CEOs. Mishra argues that generalist CEOs have lots of job opportunities. They also tend not to focus on the long-term financial soundness of the corporations—aiming to increase revenues sharply in short terms to improve their reputation. We extend Mishra’s analysis by employing firm fixed effect to its model. We find that the impact of general CEO managerial ability which is defined by Mishra (2014) as the dark side is not significant once the employ firm fixed effect is considered. This analysis assesses the effect of managerial ability on cost of capital by using Demerjian’s methodology. It was found that the impact of managerial ability on cost of capital shows a negative significant relation in line with expectations. More able managers lead to less cost of capital. This finding is in line with literature of the impact of managerial ability on company performance. We also employ firm fixed effects to our models and confirm the study’s findings. It is shown that the relation between institutional ownership and cost of capital is also significant. Further, there were many channels examined to identify possible causes of this negative relationship. It is expected that able managers disclose more information; they also help to reduce forecast error and eventually improve performance. The relationships between managerial ability and information disclosure, managerial ability and forecast error, as well as managerial ability and performance are significant. The channel effects are also explored by employing firm fixed effect, as mentioned previously. All the models present significant relationship.
Keywords: cost of equity capital; managerial ability